2009
DOI: 10.1007/s11604-009-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Mastopathic-type fibroadenoma and ductal adenoma of the breast with false-positive fluorodeoxyglucose positron emission tomography

Abstract: Positron emission tomography (PET) with (18)F-fluorodeoxyglucose (FDG) has been shown to be an effective and accurate diagnostic technique for breast cancer. However, benign breast lesions have also been reported to show a false-positive FDG uptake on PET. We present two cases of benign tumors that revealed FDG uptake on PET and were difficult to distinguish from breast cancer. A 46-year-old premenopausal woman noticed a mass in her right breast. Ultrasonography showed a hypoechoic mass with the size of 7.7 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Forty-five Table 1). The percentages of M-FA among the pathologic subtype of FA were 53% (31/59), 14% (5/35), 0% (0/1), and 50% (9/18) for intracanalicular, pericanalicular, organoid, and mastopathic types [5], respectively. The latter type displays epithelial hyperplasia, with solid and cribriform patterns that sometimes mimic intraductal carcinoma.…”
Section: Resultsmentioning
confidence: 97%
“…Forty-five Table 1). The percentages of M-FA among the pathologic subtype of FA were 53% (31/59), 14% (5/35), 0% (0/1), and 50% (9/18) for intracanalicular, pericanalicular, organoid, and mastopathic types [5], respectively. The latter type displays epithelial hyperplasia, with solid and cribriform patterns that sometimes mimic intraductal carcinoma.…”
Section: Resultsmentioning
confidence: 97%
“…However, if the epithelial components show marked hyperplastic changes and it is difficult to distinguish between a benign or malignant nature, the presence or absence of metachromasia of the mucus components constitutes a very significant supporting finding. In particular, our previous study indicated that intracanalicular and mastopathic types often show hyperplastic changes of the epithelium and could sometimes be mistaken for carcinomas 6. However, these two subtypes show a high frequency (53% and 50%, respectively) of M‐FAs among FAs 4.…”
Section: Discussionmentioning
confidence: 98%
“…The latter type displays epithelial hyperplasia, with solid and cribriform patterns that sometimes mimic carcinoma. M‐FA showed a high frequency of the intracanalicular type and mastopathic type 6. It could therefore be mistaken on histological and cytological examination between carcinomas and M‐FA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These should be included in differential diagnosis. The most common benign breast tumor, fibroadenoma, often shows low FDG uptake, but it may have high uptake mimicking a malignant lesion[ 168 , 169 ]. Asymmetrical or nodular appearance of gynecomastia also can mimic malignancy.…”
Section: Incidental Focal F-18 Fdg Uptake By Organsmentioning
confidence: 99%